Exploring the Curriculum Viability Inhibitors in an Undergraduate Dental Curriculum at Dental College HITEC-IMS - Saman Malik, Syeda Kainat Fatima, Shafaq Malik, Faiqa Hassan, M.Bilal Daud, Muhammad Farooq (Pakistan Journal of Medical & Health Sciences, 2023)
With recent advancement in medical education importance is given to evaluation, which has been included as a part of curriculum planning and implementation. By finding out the factors that inhibit the successful implementation of curriculum better outcomes can be achieved. A mixed method study was carried out at Dental college HITEC IMS. The study was conducted in two phases. In the 1st phase the quantitative assessment was carried out to find out the success of curriculum and identifying the factors that hindered in its success. In the second phase group discussion for amending the inhibitors was carried out. this study on a validated questionnaire that was prepared on scoping review and Delphi study. Under six themes inhibitors were found in five themes. No inhibitor was found under the theme of educational program. This study has helped us to pick up the inhibitors of curricular success so that we can look into possible solutions to improve the quality of curriculum of dental college. We look forward to help other institutes who are facing the same issues in their curriculum quality by suggesting solution options obtained from focused group discussion. Keywords: Curriculum viability, curriculum inhibitors, dental curriculum